2019
DOI: 10.2478/remav-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

Price Convergence in the Regional Housing Markets in Poland

Abstract: Average prices of residential real estate usually show significant variation on a regional basis. This reflects different social, economic or historical conditions for the development of these markets. In addition, research so far has not provided strong evidence supporting convergence in the level of property prices in the regional dimension. The lack of price convergence, however, does not exclude convergence in the direction and strength of price changes. The article is an attempt to answer the question of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
2
3
0
1
Order By: Relevance
“…Summarising the overall convergence analysis, it should be stressed that all research methods used in this study rejected the possibility of its occurrence across the Polish residential rental markets, which is in line with other analyses studying convergence or differentiation in the Polish real estate market; see, for example, Żelazowski ( 2019 ), Gnat ( 2016 ), Dittmann ( 2014 ), Wiśniewski and Brzezicka ( 2020 ), Tomal ( 2019a ), Tomal and Gumieniak ( 2020 ).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Summarising the overall convergence analysis, it should be stressed that all research methods used in this study rejected the possibility of its occurrence across the Polish residential rental markets, which is in line with other analyses studying convergence or differentiation in the Polish real estate market; see, for example, Żelazowski ( 2019 ), Gnat ( 2016 ), Dittmann ( 2014 ), Wiśniewski and Brzezicka ( 2020 ), Tomal ( 2019a ), Tomal and Gumieniak ( 2020 ).…”
Section: Resultssupporting
confidence: 84%
“…The empirical research to date in this area is not very extensive, and to the best of the author's knowledge only several such analyses have been developed. In particular, studies on the presence of convergence clubs in the residential market have been conducted in the USA (Kim and Rous 2012;Apergis and Payne 2012, 2019Montañés and Olmos 2013), China (Meng et al 2015;Lin et al 2015;Zhang et al 2017;Hu et al 2020), the UK (Montagnoli and Nagayasu 2015;Holmes et al 2019), Spain (Blanco et al 2016), Australia (Awaworyi Churchill et al 2018), South Africa (Apergis et al 2015) and Poland (Matysiak and Olszewski 2019;Tomal 2019aTomal , 2020a. It should be noted that almost all of the above studies analysed the convergence of sales prices in the residential market.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bruyne analyzed the pattern of spatial differentiation of housing prices in Belgium [32], while Kim [33] and Tomal [34,35] found that housing price movements in metropolitan cities in the United States and Poland are distributed in a club-clustering pattern. The analysis had led Cook [36,37], Abbott [38,39], Holmes [40][41][42], Miles [43], Zhang [44], Churchill [45], Montanes [46], Sim [47], Blanco [48], and Zelazowski [49] to propose that housing prices in the UK, US, Australia, China, Korea, Spain, Poland, and the Eurozone are represented by spatial heterogeneity, convergence, and complexity.…”
Section: Study On Spatial Differences and Correlation Effects Of Hous...mentioning
confidence: 99%
“…Konwergencja cenowa była przedmiotem badań także na wielu innych rynkach, w tym na: rynku australijskim [Ma, Liu 2015], indyjskim [Aye, Goswami, Gupta 2013], hiszpańskim [Blanco, Martin, Vazquez 2015], francuskim [Holmes, Otero, Panagiotidis 2017], polskim [Gnat 2016;Dittmann 2014;Żelazowski 2019] czy południowoafrykańskim [Das, Gupta, Kaya 2010]. Szczegółowy przegląd literatury poświęconej problematyce konwergencji rynków mieszkaniowych prezentuje tabela 5.1.…”
Section: Procesy Konwergencji Na Rynkach Nieruchomości Mieszkaniowychunclassified